PREVENTION OF DELINQUENT BEHAVIOR IN THE PHENOMENON OF JUVENILE DELINQUENCY IN JUNIOR HIGH SCHOOLS - iranda, agung; Periantalo , Jelpa; Dianesti , Annisa; Gultom , Hanna Widya; Ilham , Muhammad (Universitas Jambi, 2025)
Juvenile delinquency is social phenomenon that has negative impact in individuals, family, and society. Statistic data of BPS highlights increased trend in juvenile delinquency.This article aims for assessing school efforts dealing with juvenile delinquency, and understanding the causes and behavior patterns juvenile delinquency in school. Among programs that prevent juvenile delinquency such as pretest on knowledge of juvenile delinquency, video plays on juvenile delinquency, issues delivering, focus group discussion and icebreaking, and post test. The purpose of community service is for developing effective strategies to prevent juvenile delinquency, to create condusive and positive environment, and to support the impact of student. Keywords: Deliquency behavior, children, student